Intangible capital formation, international equity investments, and output synchronization - Guido Baldi; André Bodmer (University of Bern, Department of Economics, 2018)
We analyze the effects of intangible investment on international output synchronization. Using a dynamic stochastic general equilibrium model, we find that an increase in the importance of intangible capital leads to a higher degree of output comovement across countries. Therefore, countries in which intangible capital is more important are better suited to economic integration, such as forming a monetary union. This offers an insightful perspective on the potential relation between the considerable differences in intangible capital among Eurozone members and the discussion surrounding the Eurozone as a sub-optimal currency area. A high stock of intangible capital also tends to attract foreign equity investments, in particular foreign direct investments. We find that cross-border equity holdings in tangible and intangible capital further increase the degree of output synchronization. Our results imply that policy reforms to incentivize higher intangible capital formation and cross-border equity investments may not only foster economic growth but also improve the functioning of the monetary policy in the Eurozone.
Keywords: E22; E32; F41; 330; International Business Cycles; Investment; Cross-country Correlations; Intangible Capital